Globalisation and Education Policies in Sub-Saharan Africa (Global Journal of Human-Social Science, 2014)
The study highlights the effort of African leaders attempt in educational policy formulation and implementation from independence to globalisation era It posits that the first twenty years of independence witnessed some continued effort to evolve genuine national systems of education National consultations led to national policy documents which evolved policies- self-reliance UPE new deal curriculum development centres etc Policies were geared towards the elimination of illiteracy ignorance and poverty These efforts were cut short by political social economic etc instabilities and in the new millennium globalisation forces lent weight to the frustration of implementation of and the reframing of educational policies It recommends restoration of stability in all areas of educational systems policies and life in the region Globalisation should be made to benefit the South